Design of flexible microstrip patch antenna using rubber substrate for brain tumor detection - Ruslan, Ahmad Alhadi; Mohamad, Sarah Yasmin; Abdul Malek, Norun; Yusoff, Siti Hajar; Ibrahim, Siti Noorjannah; Mohd. Isa, Farah Nadia (IEEE, 2020)
This paper discuss and compare the performance of microstrip patch antenna with different substrates to be used for Brain Tumor Detection. The comparison of the antenna performance between natural rubber, rubber with 20% carbon filler, rubber with 25% carbon filler and rubber with 50% carbon filler are executed in this paper. The parameters that are being compared includes the antenna return loss. gain and bandwidth. The performance of the antennas is boost by applying circular electromagnetic band gap (EBG) structure on the antenna ground plane. Since the propose antenna is intended for Brain Imaging Application, the Specific Absorption Rate (SAR) performance is measured. The SAR simulation for each antenna is performed on a circular human head phantom model with six layers of bio tissue. The SAR results are then compared with the standard SAR limit defined for human head for safety purposes.